ANALISA PERENCANAAN STRATEGI BISNIS SI/TI MENGGUNAKAN METODE WARD & PEPPARD PADA PT. XYZ - Wawan Setiawan; Nurul Fajriyah (Universitas Nusa Cendana, 2022)
Planning a good system strategy and information technology is expected to help companies achieve business goals. The achievement of these business objectives must be supported by all parts of the company, so as to create a value chain that will provide margins for the company. PT. XYZ is a company engaged in the baking chocolate processing industry located in Tangerang Regency. Data collection methods used by researchers are observation, interview and literature study. Based on the interview results, there are still problems regarding the absence of a system of long-term mutually beneficial relations with customers. Lack of adequate human resources, as well as not maximizing the management of research data for chocolate product stability analysis. The method used in the research of strategic planning for Information Systems and Information Technology is Ward and Peppard. In this method several stages are carried out, including: Analysis of the business external environment using the PEST method and analysis of five Porter competition models, while analyzing the business's internal environment using a SWOT, Value Chain and CSF analysis. Then mapping the application portfolio using the Mcfarland Strategic Grid method. Based on an analysis of the external and internal environment of the business IS / IT, it is necessary to create an E-CRM system, a product information research and quality system and an employee evaluation system Keywords: Business, Planning, Strategy, Ward and Peppard